PERAN KONSEP METODE EDUTAIMENT DALAM PEMBELAJARAN BAHASA ARAB - Mahmudah, Uswatun; Suharsono, Suharsono (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
This research is motivated by an interest in the educational method in Arabic language learning, because this education is part of an effort to provide good and fun learning for students in order to get optimal results both physically and spiritually. This method has been designed in such a way that students can easily understand learning from various strategies, methods, both media according to their respective levels. With the process of this method in order to shape students into better individuals and think systematically. This article uses a qualitative approach, and this method uses the library (library research) to find data that the researcher analyzes related to the edutainment method of learning Arabic through journals, books, internet which are literate, therefore researchers will develop this edutaiment method into Arabic learning. The result of this research that edutaiment is devided to education and entertaintment. The role of edutaiment is to make a student be fun learning in the class.